The RUMiC longitudinal survey: Fostering research on labor markets in China - Mehtap Akgüç; Corrado Giulietti; Klaus F. Zimmermann (IZA Journal of Labor & Development, 2014)
This paper describes the Longitudinal Survey on Rural Urban Migration in China (RUMiC), a unique data source in terms of spatial coverage and panel dimension for research on labor markets in China. The survey is a collaboration project between the Australian National University, Beijing Normal University and the Institute for the Study of Labor (IZA), which makes data publicly available to the scientific community by producing Scientific Use Files. The paper illustrates the structure, sampling frame and tracking method of the survey, and provides an overview of the topics covered by the dataset, and a review of the existing studies based on RUMiC data.
Keywords: C81; J01; P36; R23; 330; Household survey; China; Migration; Labor markets